2022
DOI: 10.1158/1078-0432.ccr-21-3025
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib and Pembrolizumab for Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma (ALPHA Study): A Phase II Study with Biomarker Analysis

Abstract: Boehringer Ingelheim Taiwan: drug supply (afatinib) and partial research funding.Merck Sharp & Dohme Corp (I.A.) LCC, Taiwan Branch: drug supply (pembrolizumab).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…Patients receiving intensity modulated radiation therapy (IMRT) in the re-irradiation setting demonstrate improved locoregional control (52% vs 20% at 2 years), and patients who underwent gross total resection also trended towards improved locoregional control ( 35 ). While salvage surgery has been associated with improved progression free survival ( 36 ), the advantages of surgical resection prior to re-irradiation have not been universally reported when compared to re-irradiation with curative intent ( 85 ). Re-irradiation with proton therapy has also recently demonstrated promising locoregional control results (68% locoregional control at 1 year) with tolerable toxicity profiles ( 37 , 38 ).…”
Section: Considerations For Management Of Recurrent Diseasementioning
confidence: 99%
“…Patients receiving intensity modulated radiation therapy (IMRT) in the re-irradiation setting demonstrate improved locoregional control (52% vs 20% at 2 years), and patients who underwent gross total resection also trended towards improved locoregional control ( 35 ). While salvage surgery has been associated with improved progression free survival ( 36 ), the advantages of surgical resection prior to re-irradiation have not been universally reported when compared to re-irradiation with curative intent ( 85 ). Re-irradiation with proton therapy has also recently demonstrated promising locoregional control results (68% locoregional control at 1 year) with tolerable toxicity profiles ( 37 , 38 ).…”
Section: Considerations For Management Of Recurrent Diseasementioning
confidence: 99%
“…High-throughput screening of small molecule inhibitors also showed that EGFR inhibitors (including erlotinib, afatinib and gefitinib) could enhance T cell-mediated killing ( 28 ). Clinically, afatinib is being tested with pembrolizumab for platinum-refractory R/M HNC in a Phase 2 trial [NCT03695510 – ALPHA study] unveiling an impressive ORR of 41.4% ( 29 ), a drastic increase compared to 16% or 10-10.8% for pembrolizumab and afatinib monotherapy respectively ( 30 , 31 ). Biomarkers predictive of response were also investigated in this study, whereby MTAP loss or mutation was found to be associated with lower response rates, while EGFR amplification was associated with 100% ORR.…”
Section: Targeted Agents Tested In Combination With Icis In Hncmentioning
confidence: 99%
“…Biomarkers predictive of response were also investigated in this study, whereby MTAP loss or mutation was found to be associated with lower response rates, while EGFR amplification was associated with 100% ORR. On the other hand, high PD-L1 (CPS score ≥20) was associated with higher ORR (63% vs 35% in CPS score <20), albeit not statistically significant (Fisher’s exact p-value = 0.23) ( 29 ).…”
Section: Targeted Agents Tested In Combination With Icis In Hncmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by 21-gene recurrence score (OncotypeDX) showed that F/B from the tumor–stroma interface can be an independent prognostic indicator of metastasis-free survival in TME ( Desa et al, 2020 ). Based on the 29 eligible patients and 523 patients/samples of TCGA database with metastatic head and neck squamous cell carcinoma, the phase II ALPHA study by FoundationOne CDx panel demonstrated that patients with MTAP mutation or loss led to a low fraction of CD8 + T cells and was associated with suppressed immune reaction factors in the TME ( Kao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%